Natural convection in partially cooled and inclined porous rectangular enclosures - Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2007)
Natural convection heat transfer in a partially cooled and inclined rectangular enclosure filled with saturated porous medium has been investigated numerically. One of side wall has constant hot temperature and one adjacent wall is partially cooled while the remaining ones are adiabatic. Finite volume based finite difference method was applied using the SIMPLE algorithm. Governing parameters are Darcy Rayleigh number (10 <= Ra <= 1000), center of location of heater (0.1 degrees <= c <= 0.9), inclination angle (0 <= phi <= 90 degrees) and length of cooler (0.25 <= w <= 0.75). It is found that inclination angle is the dominant parameter on heat transfer and fluid flow as well as aspect ratio. (C) 2006 Elsevier Masson SAS. All rights reserved.
Keywords: porous medium; inclination angle; natural convection heat transfer